Forensic science advanced investigations - Brown, Rhonda M.; Davenport, Jackie S. (Cengage Learning, 2016)
This book is part of a comprehensive course offering as a second-level high school course in forensic science, a course area in which students have the opportunity to expand their knowledge of chemistry, biology, physics, earth science, math, and psychology, as well as associate this knowledge with real-life applications. This text builds on concepts introduced in FORENSIC SCIENCE: FUNDAMENTALS & INVESTIGATIONS, as well as introduces additional topics, such as arson and explosions. Following the same solid instructional design as the FUNDAMENTALS & INVESTIGATIONS text, the book balances extensive scientific concepts with hands-on classroom and lab activities, readings, intriguing case studies, and chapter-opening scenarios. The books exclusive Gale Forensic Science eCollection database provides instant access to hundreds of articles and Internet resources that spark student interest and extend learning beyond the book. Comprehensive, time-saving teacher support and lab activities deliver exactly what you need to ensure that students receive a solid, complete science education that keeps readers at all learning levels enthused about science. This two-book series provides a solution that is engaging, contemporary, and specifically designed for high school students. Instructors can be confident that the program has been written by high school forensic science instructors with their unique needs in mind, including content tied to the national and state science standards they are accountable to teaching. The update has a new chapter on Digital Responsibility and Social Networking.